Pengaruh Entrepreneurial Marketing dan Internet Marketing Pada UMKM Bawang Goreng Kabupaten Kuningan Terhadap Daya Saing - Yuningsih; Muhandri, Tjahja; Munandar, Jono M (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to analyze the effect of internet marketing and entrepreneurial marketing on the competitive advantages of fried onion MSMEs in Kuningan Regency. The analytical method used is descriptive analysis and structural analysis with the PLS-SEM (Partial Square Least-Structural Equation Modeling) approach. The results of this study indicate that the characteristics of fried onion business actors are dominated by women as much as 67 percent, the age of the majority of business actors is in the productive age range of 30-40 years, and in general, they have a high school / vocational / MA education level and their initial job before starting a business is never or not working or housewives. The majority of business actors have the reason that the business they run follows in the footsteps of their parents/relatives and the majority of the businesses they run are 1-10 years old. SEM analysis indicates that internet marketing has a positive influence on entrepreneurial marketing and competitive advantages, as well as entrepreneurial marketing which has a positive influence on competitive advantages. Managerial implications that can be carried out by business actors are participating in skills development training using digital technology and actively using the internet to expand marketing reach. For the government by making skills development training using digital technology for marketing. Keywords: competitive advantages, entrepreneurial marketing, internet marketing, SEM PLS, SMEs